Effects of sodium/glucose cotransporter 2 inhibitors on the coagulation profile in patients with coronary-artery disease and type 2 diabetes mellitus: a retrospective cohort study - Qin, XiaoYue; Song, GuoBin (Frontiers in Cardiovascular Medicine, 2025)
AimsPatients with coronary-artery disease (CAD) and type 2 diabetes mellitus (T2DM) are often in a hypercoagulable state and have an increased thrombosis risk. We aimed to evaluate the effects of sodium/glucose cotransporter 2 inhibitors (SGLT2is) on coagulation function and explore their potential role in regulating coagulation in these patients.MethodsWe conducted a retrospective cohort study between June 2020 and June 2024 in patients with CAD and T2DM. Eligible patients were assigned to either the SGLT2i or non-SGLT2i group. Clinical information, laboratory tests, and echocardiographic (EKG) examination results were retrieved. We performed inter- and intragroup comparisons of coagulation function measurements before and after treatment, and also conducted regression analysis to assess the impact of treatment on coagulation function.ResultsA total of 121 patients were included, with 49 and 72 in the SGLT2i and non-SGLT2i groups, respectively. After 30 days of treatment, antithrombin III (AT-III) activity increased by 5.39% (P = 0.026) in the SGLT2i group, but slightly decreased in the non-SGLT2i group. SGLT2 is also decreased D-dimer levels by 95 mg/L (group P = 0.051, group:time P = 0.075). Further regression analysis showed a significant interaction between group and time for AT-III and D-dimer (P = 0.026 and P = 0.039). Additionally, prothrombin time (PT) showed a slight increase after SGLT2i treatment.ConclusionSGLT2is could affect coagulation function by prolonging coagulation time and increasing anticoagulatory activity in patients with T2DM and CAD. These drugs could be used to ameliorate hypercoagulable states and reduce thrombosis risk in these patients.